Penyusunan RUU Revisi TNI di Tengah Penolakan Masyarakat - Ikhwan Nur Ramadhan; Damar Arrya Akbar A; Fajar Kurniawan; Herdandi Bagus A.P. (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study explores how the drafting process of the Bill (RUU) for the Revision of the Indonesian National Armed Forces (TNI), which was approved to become Law Number 3 of 2025, occurred amidst massive public protests, with an emphasis on violations of the principles of openness, participation, and accountability as regulated in the 1945 Constitution and Law Number 12 of 2011 concerning the Formation of Legislative Regulations. The public's rejection illustrates the potential for abusive law making, threats to civilian dominance, and the possibility of a return to the dual function of the military from the New Order period, supported by protests, petitions from civil society organizations such as NU, WALHI, and KONTRAS, as well as an application for constitutional review to the Constitutional Court. Adopting the perspective of Habermas’s theory of deliberative democracy and Weber’s concept of legitimacy, this research asserts that the argument for the annulment of this Bill is growing stronger, in order to uphold democratic law making and the protection of human rights.